Enhanced alveolar macrophage-mediated antigen-induced T-lymphocyte proliferation in sarcoidosis. - Venet, A (1985)
Expansion of T-lymphocyte numbers is a characteristic feature of the alveolitis of pulmonary sarcoidosis. One mechanism that may influence the numbers of T-lymphocytes in the lung is the process of antigen presentation in which alveolar macrophages, in the presence of antigen, induce T-lymphocytes to replicate. To evaluate this process in sarcoidosis, alveolar macrophages were obtained by bronchoalveolar lavage, pulsed with tetanus toxoid, and co-cultured with purified autologous T cells. Strikingly, antigen-pulsed alveolar macrophages from sarcoid patients induced more than a twofold increase in autologous T-lymphocyte proliferation compared with the response seen using cells from normal or patients with idiopathic pulmonary fibrosis (P less than 0.001), all comparisons). In contrast, when monocytes were used as the antigen presenting cell, no significant differences were observed in T cell proliferation induced by antigen among the three groups. The enhanced T-lymphocyte proliferation induced by sarcoid alveolar macrophages was not dependent on the compartment from which the T cells were derived, and was independent of the specific antigen used. One possible explanation for augmented antigen presentation seen in sarcoid is that an increased percentage of sarcoid alveolar macrophages express HLA-DR or HLA-DS surface antigens. However, most normal and sarcoid alveolar macrophages express HLA-DR and HLA-DS surface antigens, and the percentage of macrophages expressing these antigens was not significantly different in the two groups. Thus, while the mechanisms of the enhanced antigen presentation in the sarcoid lung are unknown, the process of antigen-driven, alveolar macrophage-modulated lung T cell proliferation may explain, at least in part, the expansion of lung T-lymphocyte numbers that characterizes this disease.